2009
DOI: 10.1111/j.1399-5618.2009.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

The history of lithium therapy

Abstract: The use of lithium in psychiatry goes back to the mid-19th century. Early work, however, was soon forgotten, and John Cade is credited with reintroducing lithium to psychiatry for mania in 1949. Mogens Schou undertook a randomly controlled trial for mania in 1954, and in the course of that study became curious about lithium as a prophylactic for depressive illness. In 1970, the United States became the 50th country to admit lithium to the marketplace. Meanwhile, interest in lithium for the prophylaxis of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
170
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 28 publications
2
170
0
2
Order By: Relevance
“…Lithium, which came into systematic use as a mood stabilizer shortly after World War II [308], is the oldest psychiatric drug in Western medicine with folk roots that may stretch back to antiquity [309]. It remains one of the staples of treatment in BD, with a significant subclass of patients exquisitely responsive to it.…”
Section: Concluding Remarks: Therapeutic Considerationsmentioning
confidence: 99%
“…Lithium, which came into systematic use as a mood stabilizer shortly after World War II [308], is the oldest psychiatric drug in Western medicine with folk roots that may stretch back to antiquity [309]. It remains one of the staples of treatment in BD, with a significant subclass of patients exquisitely responsive to it.…”
Section: Concluding Remarks: Therapeutic Considerationsmentioning
confidence: 99%
“…The lower dose of lithium used in our study is nearly four times lower than the regular maintenance dose for lithium's psychotropic indication in the treatment of bipolar disorder 35 , which may suggest that the lithium levels needed to improve bone-healing come with minimal risk of acute toxicity. Furthermore, while there are clinically major long-term concerns-including hyperparathyroidism, hypothyroidism, and nephrogenic diabetes insipidus-in patients managed with lithium [36][37][38] , these long-term side effects may be less relevant in short-term lithium use for bone-healing.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its numerous side effects, the use of lithium was discontinued for a number of decades, until its reintroduction at the end of the 1940s, when it was shown that manic episodes were related to the accumulation of uric acid in patients' brains (Shorter, 2009;Salvadore et al, 2010b). Because of its neuroprotective and anti-psychotic properties, lithium has been used for acute treatment, prevention of relapse and maintenance of stable mood (Gray and McEwen, 2013;Hübers et al, 2014).…”
Section: Treatments Available For Bipolar Disordermentioning
confidence: 99%